NF135.C10: a new Plasmodium falciparum clone for controlled human malaria infections - Teirlinck, Anne C.; Roestenberg, Meta; Vegte-Bolmer, Marga van de (The journal of infectious diseases, 2013)
We established a new field clone of Plasmodium falciparum for use in controlled human malaria infections and vaccine studies to complement the current small portfolio of P. falciparum strains, primarily based on NF54. The Cambodian clone NF135.C10 consistently produced gametocytes and generated substantial numbers of sporozoites in Anopheles mosquitoes and diverged from NF54 parasites by genetic markers. In a controlled human malaria infection trial, 3 of 5 volunteers challenged by mosquitoes infected with NF135.C10 and 4 of 5 challenged with NF54 developed parasitemia as detected with microscopy. The 2 strains induced similar clinical signs and symptoms as well as cellular immunological responses.
Electronically published 27 November 2012
Gesehen am 03.02.2022